Impact of Distinct Carbon Substrates on the Proliferation of Antimicrobial-Producing Microbes - Umaru, Isaac John; Danjuma, Tyem Lawal; Akem, Ingwu Joseph; Salman, Julius Ishaya; Ahmed, Maryam Usman; Umaru, Hauwa A. (Darul Yasin Al Sys, 2026)
Microbial production of antimicrobial compounds remains a fundamental area of biotechnology and pharmaceutical development, and its efficiency is strongly influenced by the carbon source available in the growth medium, which functions not only as an energy substrate but also as a regulator of microbial metabolism and secondary metabolite synthesis. This study aimed to evaluate the effects of five carbon sources—glucose, lactose, sucrose, starch, and glycerol—on microbial biomass yield, strain-specific growth preferences, metabolic compatibility, antimicrobial potency, inhibition zones, and bioactive metabolite production. Seven microbial strains, including Streptomyces, Bacillus, Pseudomonas, Actinomyces, and Clostridium, were cultured in media supplemented with each carbon source. Biomass yield was measured gravimetrically, growth rate indices were calculated on a scale of 0–10, antimicrobial potency was assessed using zone of inhibition assays against S. aureus, E. coli, P. aeruginosa, and K. pneumoniae, and metabolite yield was quantified in mg/L using spectrophotometric analysis. All experiments were conducted in triplicate. The findings showed that glucose produced the highest biomass yield and growth rates across all strains, with Bacillus and Pseudomonas each scoring 10. Lactose demonstrated selective effectiveness, particularly for Streptomyces, whereas sucrose supported moderate growth and selective antimicrobial activity. In contrast, starch and glycerol consistently resulted in low biomass production and minimal antimicrobial potency. The zone of inhibition results further confirmed that glucose and lactose were the most effective substrates, with inhibition zones exceeding 20 mm. Similarly, metabolite yield was highest with glucose (120 ± 5.4 mg/L) and lactose (115 ± 4.9 mg/L), while glycerol produced the lowest yield (30 ± 1.5 mg/L). The study concludes that carbon source selection plays a critical role in microbial proliferation and antimicrobial compound production, with glucose and lactose emerging as the most suitable substrates for broad-spectrum antimicrobial activity and high metabolite yield. These findings contribute practical evidence for optimizing fermentation strategies according to microbial metabolic profiles to enhance antimicrobial synthesis.